2018
DOI: 10.12659/msm.909449
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Significance of Serum Levels of Nerve Growth Factor and Brain Derived Neurotrophic Factor in Diabetic Peripheral Neuropathy

Abstract: BackgroundOur study aimed to explore the levels of nerve growth factor (NGF) and brain derived neurotrophic factor (BDNF) in healthy participants, type 2 diabetes mellitus (T2DM) patients, and diabetic peripheral neuropathy (DPN) patients in order to find their effects on DPN.Material/MethodsThe clinical data of 110 healthy participants (age: 57.3±8.2 year, height: 165.4±5.5 cm, weight: 64.1±7.5 kg), 83 T2DM patients (age: 56.5±7.9 year, height: 164.8±6.2 cm, and weight: 63.6±6.6 kg), and 65 DPN patients (age:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…(22) The relevance of BDNF in peripheral nerve injury and neuropathic pain was highlighted in studies on diabetic peripheral neuropathy. (23) The decreased in serum levels of BDNF and NGF has been demonstrated in patients with diabetic peripheral neuropathy, suggesting that multiple deficits in these neurotrophic factors could precede clinically the detectable nerve dysfunction. (23) The decreased of cytoplasmic expression and secretion of BDNF in hSC treated with sML could be associ-ated with a declined neurotrophic and immunomodulatory character of hSC, hampering the tissue integrity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(22) The relevance of BDNF in peripheral nerve injury and neuropathic pain was highlighted in studies on diabetic peripheral neuropathy. (23) The decreased in serum levels of BDNF and NGF has been demonstrated in patients with diabetic peripheral neuropathy, suggesting that multiple deficits in these neurotrophic factors could precede clinically the detectable nerve dysfunction. (23) The decreased of cytoplasmic expression and secretion of BDNF in hSC treated with sML could be associ-ated with a declined neurotrophic and immunomodulatory character of hSC, hampering the tissue integrity.…”
Section: Discussionmentioning
confidence: 99%
“…(23) The decreased in serum levels of BDNF and NGF has been demonstrated in patients with diabetic peripheral neuropathy, suggesting that multiple deficits in these neurotrophic factors could precede clinically the detectable nerve dysfunction. (23) The decreased of cytoplasmic expression and secretion of BDNF in hSC treated with sML could be associ-ated with a declined neurotrophic and immunomodulatory character of hSC, hampering the tissue integrity. The neuroprotective role of SC-derived BDNF was demonstrated by Hou et al study, in which BDNF-enriched SC enhanced in vitro its proliferative and secretory functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum levels of BDNF in the control group were higher compared to the patients with diabetes mellitus type 2. Qin Sun et al revealed that BDNF levels were correlated with the course of disease for patients, fasting C-peptide, 2-hour postprandial C-peptide level, glycosylated hemoglobin level, and 24-hour urinary microalbumin excretion [39].…”
Section: Bdnf and Chronic Complications Of Diabetesmentioning
confidence: 99%
“…Nerve growth factor is important for the development and differentiation of sensory neurons during embryogenesis ( Levi-Montalcini, 1987 ; Li et al, 2017 ; Sun et al, 2018 ). Painful signals on the skin were transmited to the spinal cord and brain by myelinated Aδ and unmyelinated C sensory nerve fibers ( Adrienne and Dubin, 2010 ).…”
Section: Resultsmentioning
confidence: 99%